UPAYA PENINGKATAN LITERASI MAHASISWA MELALUI PELATIHAN MENULIS KREATIF DI KOTA PADANG PANJANG - Mezia Kemala Sari; Bahren Bahren; Zuiyardam Zuiyardam (BULETIN ILMIAH NAGARI MEMBANGUN, 2020)
Writing is a language skill that is used to communicate indirectly. The ability and willingness to write students who are involved in journalism, such as creative writing, are minimal. To address this, it is necessary to solve the classic problems of learners, especially students in the world of writing and literacy. This activity involved students in the Education and Teacher Training Department. It is hoped that this activity can increase students' willingness and ability to write in the field of creative writing. This activity is carried out in the form of training activities with direct assistance during training and after training. Writing training activities are carried out in an exciting and fun way, using image media for the student level. So that students are not bored, besides the lecture method, it is also equipped with training. The training method is carried out using efficient delivery, discussion, and hands-on practice, divided into three sessions: imagination, fiction, and expression. Through this training activity, participants are expected to increase their willingness and ability in writing. There will be more opportunities to publish creative writing results online with available means and channels. After the training was carried out, there was an increase in his abilities and willingness, especially in making Minang poetry and Indonesian language poetry fictional prose created in a short time. Furthermore, the activity was closed with the publication of their writing on the minangsatu.com page, which would continue periodically.